Impact of Medications for Opioid Use Disorder on Discharge Against Medical Advice Among People Who Inject Drugs Hospitalized for Infective Endocarditis. Issue 2 (12th January 2020) - Suzuki, Joji; Robinson, Diana; Mosquera, Matthew; Solomon, Daniel A.; Montgomery, Mary W.; Price, Christin D.; Johnson, Jennifer A.; Martin, Bianca; Liebschutz, Jane W.; Schnipper, Jeffrey L.; Weiss, Roger D.
Abstract : Background and Objectives: The impact of medications for opioid use disorder (MOUD) on against medical advice (AMA) discharges among people who inject drugs (PWID) hospitalized for endocarditis is unknown. Methods: A retrospective review of all PWID hospitalized for endocarditis at our institution between 2016 and 2018 ( n  = 84). Results: PWID engaged with MOUD at admission, compared with those who were not, were less likely to be discharged AMA but this did not reach statistical significance in adjusted analysis (odds ratio [OR], 0.22; 95% confidence interval [CI], 0.033‐1.41; P   = .11). Among out‐of‐treatment individuals, newly initiating MOUD did not lead to significantly fewer AMA discharges (OR, 0.98; 95% CI, 0.26‐3.7; P  = .98). Conclusion and Scientific Significance: PWID hospitalized for endocarditis are at high risk for discharge AMA but more research is needed to understand the impact of MOUD. (Am J Addict 2020;29:155–159)